2014
DOI: 10.2337/db13-1440
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of GLP-1 Receptor–Expressing Cells Using a New Transgenic Mouse Model

Abstract: GLP-1 is an intestinal hormone with widespread actions on metabolism. Therapies based on GLP-1 are highly effective because they increase glucosedependent insulin secretion in people with type 2 diabetes, but many reports suggest that GLP-1 has additional beneficial or, in some cases, potentially dangerous actions on other tissues, including the heart, vasculature, exocrine pancreas, liver, and central nervous system. Identifying which tissues express the GLP-1 receptor (GLP1R) is critical for the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
406
3
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(460 citation statements)
references
References 28 publications
36
406
3
9
Order By: Relevance
“…GLP1R is widely expressed in pancreatic islets, as well as in the brain, heart, kidney, and gastrointestinal tract (19 -21). Specifically in the pancreas, GLP1R expression was confirmed in beta and delta cells; however, it was 10-fold lower in delta cells when quantified by quantitative real time PCR (qPCR) (21). In the alpha cell population, very low expression of GLP1R was detected (21).…”
Section: Glp1mentioning
confidence: 99%
See 2 more Smart Citations
“…GLP1R is widely expressed in pancreatic islets, as well as in the brain, heart, kidney, and gastrointestinal tract (19 -21). Specifically in the pancreas, GLP1R expression was confirmed in beta and delta cells; however, it was 10-fold lower in delta cells when quantified by quantitative real time PCR (qPCR) (21). In the alpha cell population, very low expression of GLP1R was detected (21).…”
Section: Glp1mentioning
confidence: 99%
“…Specifically in the pancreas, GLP1R expression was confirmed in beta and delta cells; however, it was 10-fold lower in delta cells when quantified by quantitative real time PCR (qPCR) (21). In the alpha cell population, very low expression of GLP1R was detected (21). Like other B class GPCRs, GLP1R signals through the G s protein complex and activates adenylyl cyclase, which converts ATP into cAMP (22,23).…”
Section: Glp1mentioning
confidence: 99%
See 1 more Smart Citation
“…13 It was reported that native GLP-1 infusion for several hours to individuals with type 2 diabetes resulted in improvement in endothelial function. 27,28 Although both GLP-1 and cleaved GLP-1, such as GLP-1(9-36) and GLP-1 (28)(29)(30)(31)(32)(33)(34)(35)(36), may cause these effects, a study comparing the effect of native GLP-1 on vascular function with or without of sitagliptin to prevent an increase of the cleaved form of GLP-1 resulted in no detectable changes in both groups. 29 Although the existence of the GLP-1 receptor on the vascular endothelium has been suggested, recent accumulating evidence showed that the endothelium does not possess the GLP-1 receptor, 30,31 but there is currently no consensus.…”
Section: The Effect Of Incretin-related Therapy On Endothelial Cell Fmentioning
confidence: 99%
“…The exact role of GLP-1 released from these neurons is still under investigation, but they seem to be involved in the mediation of reduced eating in response to aversive stimuli or in sickness anorexia. 12 Further, recent data indicate that locally released GLP-1 also contributes to the physiological control of eating and body weight (for example, Kanoski et al, 13 Hisadome et al 14 and Richards et al 15 ) because the knockdown of GLP-1 in the nucleus of the solitary tract leads to increased eating, body weight and adiposity. 16 …”
Section: Production Site and Secretion Of Amylin And Glp-1mentioning
confidence: 99%